An Iconological Approach to Study of Female Motifs in Themes of Graffiti in Saqanefar of Kijatekiyeh, Babol - samareh rezaei; atieh Youzbashi (زن در فرهنگ و هنر)
Saqanefars are structures from the Qajar period that are derived from the indigenous and ritual architecture of Mazandaran. In contrast to comparable structures, Saqanfar Kijatekiyeh in Babol is characterized by a plethora of pictorial themes that are specifically focused on women. This research aims to explore the themes and significance of women's roles in these murals. The research questions are as follows: -What is the reason for the increased prevalence of women's motifs in Saqanfar Kijatekiyeh Babol in comparison to other Saqanefars? -What are the reasons for the prominence of women in these murals? - Which themes are illustrated in the murals of Saqanfar Kijatekiyeh, Babol? The research employs a descriptive-analytical method, which involves the non-random selection of specific images from epic, otherworldly, symbolic, and quotidian activity motifs and their description using an iconological approach. Significant developments and changes in women's status were reflected in the Qajar era, which saw a zenith in the redefining of women's roles in society, family, and art. The northern regions of Iran underwent a change in gender concepts as a result of their geographical and livelihood conditions. The development of women's roles is significantly influenced by historical, social, political, and cultural factors. The Tekiyeh building's simultaneity with the Qajar period, the fundamental changes in social relations, clothing styles, political positions, and aesthetic concepts of women, as well as the abundance of women's images, suggest a direct connection between these motifs and the political and social developments of the era. This is indicative of the impact of indigenous artists on the representation of political and social conditions within a particular historical context.